Arbitration in the South China Sea: Legal and Geopolitical Ramifications: Arbitrase di Laut Cina Selatan: Konsekuensi Hukum dan Geopolitik - Somomoeljono, Suhardi; Hardy, Jurisdito Hutomo (Universitas Muhammadiyah Sidoarjo, 2023)
The present research scrutinizes the arbitration case between the Philippines and the People's Republic of China concerning the contested maritime zones in the South China Sea, a global hotspot for territorial disputes, rich natural resources, and strategic naval passages. Utilizing a normative legal research methodology coupled with a descriptive-analytical approach, this study carefully examines international legal frameworks, including UNCLOS, and draws upon a diverse range of data sources like legal documents, official statements, and scholarly literature to dissect the nuances of the South China Sea dispute. The findings reveal that the arbitration process, initiated by the Philippines in 2013 and culminating in a 2016 verdict favoring several of its claims, not only holds the promise to fortify international maritime law and foster regional stability but also underscores the critical role of diplomatic efforts in actualizing comprehensive solutions. Nonetheless, the endeavor is not without its pitfalls, notably the absence of stringent sanctions and implementation challenges. Furthermore, the arbitration verdict significantly influences the Philippines-PRC bilateral relations, affecting territorial claims and regional economies, while reaffirming UNCLOS's authority in governing international maritime conflicts. Therefore, the research advocates for sustained diplomatic initiatives and collaboration as a complementary pathway to arbitration, envisioning a harmonious resolution to the complex and multifaceted South China Sea dispute. Highlights: The arbitration case between the Philippines and the PRC reaffirmed the crucial role of UNCLOS in guiding international maritime disputes and fostering regional stability. Despite the potential to enhance international maritime law and prevent conflicts, the arbitration process faces challenges in terms of enforcing sanctions and ensuring comprehensive implementation. The arbitration verdict has deep-seated implications on Philippines-PRC bilateral relations, impacting territorial claims, economic prospects, and necessitating sustained diplomatic efforts for a more cohesive resolution to the South China Sea dispute. Keywords: South China Sea, International Arbitration, UNCLOS, Philippines-PRC Relations, Maritime Law.